Evaluation of strategy of power generation business under large-scale integration of renewable energy - Gert Brunekreeft; Marius Buchmann; Toru Hattori; Roland Meyer (Jacobs University Bremen, Bremen Energy Research (BER), 2016)
The German energy transition massively alters the market structure of electricity supply and forces incumbent electric utilities to rethink their business strategies. We analyze three main developments that undermine the former market dominance of the 'Big 4' incumbents in Germany. First, nuclear phase-out reduces their market shares and creates financial risk of nuclear waste decommissioning. Second, the large-scale integration of renewables fosters market entry from third parties and intensifies competition. Third, a possible coal-phase out in combination may have positive effects on market revenues but tends to increase regulatory risk. In total, incumbents face 'disruptive Challenges' and need to find new value-creating products and services beyond sole energy supply. Promising focus areas are renewable energies, the distribution business, and smart, customer-oriented solutions.
Keywords: L94; L11; 330; electric utilities; market structure; firm strategy